Hubungan Partisipasi Penyusunan Standar, Keketatan Standar dan Insentif Berbasis Standar dengan Kinerja (Pengujian Hubungan Langsung dan Tidak Langsung) - Etty Murwaningsari (KINERJA, 2009)
This  research  aims  to  investigate  the  relationship  between  participative standard  setting, standard  tightness  and  standard-based  incentives  toward public  accountant  performance  and work-related stress. The research examined 16 Jakarta-based public accounting firms in 2007 involving  213  respondents––112  from  big-four  public  accounting  firms  and  101  from  non-big-four public accounting firms. The statistical method used to test the hypothesis is the Structural Equation Model (SEM). Empirical results from observing a big-four public accounting firm using a direct model examining five variables show that four variables have significant correlation, while an  indirect  model  examining  six variables  results  in  two  variables  have  significant  correlation. Moreover, an observation of a non-big-four public accounting firm using a direct model examining five  variables  show  that  four  variables  have  significant  correlation, while  examination  of  six variables using an indirect model found that five variables have significant correlation.